Fake news detection: a brief quantitative text analysis - Vasileiou, Maria Eleni (Open Schools Journal for Open Science, 2021)
Fake news has always been an issue, but the worldwide chaos caused by the Covid-19 pandemic has brought a new wave of fabricated news stories to the surface. This is the first pandemic in history in which technology and social media in particular play a crucial role in peoples’ safety and information. However, the same technology is allowing for an overabundance of information, part of which consists of misinformation with harmful intentions, which endangers public health. The importance of this matter is reflected on the need for a definition for this new phenomenon: an infodemic.1 This brief research attempts to investigate the effectivity of a limited quantitative analysis in online articles as a tool to determine an article’s validity.